SHV-12-Like Extended-Spectrum-β-Lactamase-Producing Strains of Salmonella enterica Serotypes Babelsberg and Enteritidis Isolated in France among Infants Adopted from Mali - Weill, François-Xavier (American Society for Microbiology, 2004)
From December 2002 to June 2003, 14 cultures of Salmonella enterica serotype Babelsberg and 6 cultures of serotype Enteritidis, isolated in France from internationally adopted children, were identified at the French National Reference Center for Salmonella. All serotype Babelsberg isolates were related, as determined by pulsed-field gel electrophoresis, and all serotype Enteritidis strains displayed the same phage type. All serotype Enteritidis and seven serotype Babelsberg isolates produced an SHV-12-like extended-spectrum β-lactamase as determined by sequencing of PCR products and by isoelectrofocusing. Some serotype Enteritidis isolates exhibited additional antimicrobial resistance (aminoglycosides, tetracycline, chloramphenicol, sulfonamides, and trimethoprim). Our investigation indicated that these Salmonella isolates were certainly acquired in the same orphanage in Bamako, Mali, before the children were adopted by French families. An inappropriate use of ceftriaxone was probably the cause of the emergence of such strains. There is an urgent need to determine the origin of the contamination and to introduce adequate antibiotic protocols into this orphanage to prevent further transmission and dissemination. Screening for infections and follow-up, adapted to the origin of the internationally adopted children, should be recommended.